The first capybaras (Rodentia, Caviidae, Hydrochoerinae) involved in the Great American Biotic Interchange - Vucetich, María Guiomar (2015)
The new combination Phugatherium dichroplax nov. comb. (Ahearn and Lance) is proposed for the North American species “Neochoerus” dichroplax Ahearn and Lance, and “N.” cordobai Carranza-Castañeda and Miller. Its age range is here expanded (late Early Blancan—latest Blancan; Piacenzian—Gelasian), being the youngest species of Phugatherium and thus extending the biochron of the genus into the early Pleistocene. This is the first mention of a Pliocene South American lineage of capybaras crossing the Panamanian bridge, implying the recognition of a third lineage of capybaras involved in the Great American Biotic Interchange. The proposed North American origin of the genus Neochoerus is discussed.